2022
DOI: 10.11646/phytotaxa.530.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Type studies on two Paxillus species (Paxillaceae, Boletales) described from China

Abstract: Types and recently collected samples of two Paxillus species namely P. rhytidophyllus and P. yunnanensis, originally described from southwestern China, were critically restudied based on morphology and molecular phylogenetic data of DNA sequences from the large subunit of the nuclear ribosomal RNA (nrLSU), the nuclear ribosomal internal transcribed spacer (ITS), and the translation elongation factor 1-α (tef1-α). The results showed that these two species belong to Boletinellus and Tricholomopsis, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 508 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Phylogenetic analysis indicated that T. yunnanensis and T. galeata are conspecific. Although Mao et al ( 2021 ) did not find any pleurocystidia in T. galeata and Liu et al ( 2022 ) regarded the pileipellis as palisadoderm, we observed the presence of pleurocystidia and regarded the pileipellis as a cutis with transition to a trichoderm in T. yunnanensis .…”
Section: Taxonomycontrasting
confidence: 87%
See 1 more Smart Citation
“…Phylogenetic analysis indicated that T. yunnanensis and T. galeata are conspecific. Although Mao et al ( 2021 ) did not find any pleurocystidia in T. galeata and Liu et al ( 2022 ) regarded the pileipellis as palisadoderm, we observed the presence of pleurocystidia and regarded the pileipellis as a cutis with transition to a trichoderm in T. yunnanensis .…”
Section: Taxonomycontrasting
confidence: 87%
“…Notes : Tricholomopsis yunnanensis was first described in southwestern China as Paxillus yunnanensis by Zang and Zeng ( 1978 ). The type was restudied by Liu et al ( 2022 ), who placed it into Tricholomopsis as T. yunnanensis . Phylogenetic analysis indicated that T. yunnanensis and T. galeata are conspecific.…”
Section: Taxonomymentioning
confidence: 99%
“…It is found across the Northern Hemisphere mostly in wetlands and often forms symbiotic relationships with different types of plants, such as hardwood and coniferous trees. These mushrooms are versatile, thriving in various ecosystems, even in degraded or contaminated areas (Cagigal and Sánchez, 2017;Liu et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Few taxa of this genus have biochemical properties and play a bene cial role in agroecology i.e., nutrient cycling, aiding host plants in acquiring essential nutrients and enhancing their tolerance to heavy metals (Sayyed and Hussain 2020). Up until now, seventy one (71) different species have been identi ed and described as belonging to the Paxillus genus worldwide (Liu et al 2022, https://www.indexfungorum.org/names/names.asp). In Pakistan, this genus seems new as no report of Paxillus has been found in previously published literature.…”
Section: Introductionmentioning
confidence: 99%